Cost management of e-business projects - Ciechan-Kujawa, Marlena; Goldmann, Katarzyna (Copernican Journal of Finance & Accounting, 2013)
Business Model based on wide-ranging ICT solutions is becoming more and more popular. Projects implemented under this model to improve the efficiency, speed and innovation. They have also a new way of creating value in the organization. The specifics of the location of their and the functioning of the Internet necessitates a different approach to the management of certain aspects of e-business projects compared to the traditional. The purpose of the article is an indication of these differences. Particular attention was paid to the financial aspects, including the costs incurred on the various stages of the planning of projects, their implementation, deployment and management throughout the life cycle.